Thermally Sprayed Coatings for High-Temperature Applications - Di Girolamo, Giovanni; Pagnotta, Leonardo (Recent Patents on Materials Science, 2011)
Thermally sprayed coatings are very effective tools for high-temperature applications in energy and aerospace industries. They are applied on the surface of complex components as those of turbine engines in order to provide enhanced thermal and environmental protection against heat transfer, high-temperature oxidation, hot-corrosion, wear and erosion. Thereby, they are suitable to significantly increase the capability and the durability of these components as well as the efficiency of turbine engines, in accordance with the growing demand for higher performance and lower environmental impact. The recent developments about anti-oxidant coatings, thermal barrier coatings (TBCs), environmental barrier coatings (EBCs), abradable coatings and wear resistant coatings are summarized in this paper. The patents related to these applications are reviewed.
Keywords: thermal spraying